Comparative Study of Phenolic Profile and Content in Infusions and Concentrated Infusions of Buddleja Scordioides Treated by High-Intensity Pulsed Electric Fields (HiPEF) - Jesús Omar Díaz-Rivas; José Alberto Gallegos-Infante; Aurora Valdez-Fragoso; Nuria Elizabeth Rocha-Guzmán; Rubén Francisco González-Laredo; Alfredo Rodríguez-Ramírez; Claudia Ivette Gamboa-Gómez; Martha Rocío Moreno-Jiménez (Beverages, 2018)
The effect of high-intensity pulsed electric fields (HiPEF) has been reported on the microbial resistance of fruit juices and beverages. However, the influence of HiPEF on bioactive compounds in herbal infusions is still limited. The objective of the present work was to evaluate chemical stability of polyphenols of infusions from Buddleja scordioides or Salvilla under thermal processing (concentrates) followed by HiPEF treatments. Buddleja infusions were prepared at 1% w/v of salvilla, heated, filtered and concentrated in a thin falling film evaporator. Three different HiPEF treatments were applied to Buddleja scordioides concentrated beverages. The percentage of pulse rate was 25 and 90%; output temperature, 18.3 ± 1 °C; and the frequency range, 100, 300 and 400 Hz. The feed flow was 0.5 L/h. DPPH radical scavenging assay, inhibition of Nitric Oxide activity and analysis of phenolic acids and flavonoids by UPLC-ESI-MS/MS were determined. ANOVA one-way analysis and Tukey test (p < 0.05) were used to analyze results. Concentration process increases the amount of flavonols; however, the use of HiPEF produces a minor reduction on antioxidant capacity. The use of HiPEF at 1000 kJ/kg and 1100 kJ/kg displays a similar profile on phenolic acids between HiPEF-treated beverages and concentrates, showing that the use of HiPEF may be a promissory technology in the processing practices of herbal infusions.